2006
DOI: 10.1007/s00431-006-0107-2
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi’s sarcoma in a child with Wiskott-Aldrich syndrome

Abstract: This observation expands the spectrum of primary immunodeficiencies associated with KS in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 27 publications
1
30
0
2
Order By: Relevance
“…We previously hypothesized that this peculiar KS form may be related to an early and massive KSHV infection in genetically susceptible individuals [14]. In some classical KS in children, diverse genetic defects have been reported [59], [60], [61]. Similar studies need to be performed in children suffering from endemic KS in central Africa.…”
Section: Discussionmentioning
confidence: 98%
“…We previously hypothesized that this peculiar KS form may be related to an early and massive KSHV infection in genetically susceptible individuals [14]. In some classical KS in children, diverse genetic defects have been reported [59], [60], [61]. Similar studies need to be performed in children suffering from endemic KS in central Africa.…”
Section: Discussionmentioning
confidence: 98%
“…One patient (P12) had 2 different malignant complications (human herpesvirus 8-associated Kaposi sarcoma and an intracerebral, EBV-related, lymphoproliferative disorder) that were diagnosed at 19 and 23 months of age, respectively (reported in Picard et al 22 ; Table 2). He underwent HSCT with his 9.5/10 HLA-matched father (mismatch of a subtype of HLA-A on allelic HLA typing) after treatment with paclitaxel for Kaposi sarcoma and rituximab (combined with intrathecal infusions of rituximab and methotrexate because of intracranial hypertension) for the B-cell lymphoproliferative disorder.…”
Section: Tumorsmentioning
confidence: 99%
“…3 The condition is caused by hemizygous mutations in the WAS gene (Xp11. [22][23], which encodes the WAS protein (WASp). 4 The latter is expressed exclusively in hematopoietic cells and has a major role in actin polymerization, regulation of cytoskeleton reorganization, signal transduction, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Grossman et al 26 reported HHV-8-related HLH in 2 triplets with familial HLH due to perforin gene mutations. HHV-8-related HLH has been also reported in immunosuppressed patients who underwent renal transplantation or rarely, in HIV-negative adults.…”
Section: Discussionmentioning
confidence: 99%